Experimental study on the treatment of deep miscellaneous fill foundation in Xinjiang by vibrating rod compaction method - Xuejun Liu; Jingchun Xue; Wei Mao; Liangfu Xie; Guangyin Du (Scientific Reports, 2024)
Abstract Currently, the treatment of miscellaneous fill foundations, composed of a mixture of domestic garbage, construction solid waste, and natural soil, presents a significant challenge in urban peripheral engineering construction. This paper discusses the application of vibrating rod compaction technology for foundation treatment in Xinjiang. It evaluates the effectiveness of cross-section vibrating rod compaction equipment in reinforcing fine-grained miscellaneous fill foundations. The study analyzes the impact of construction disturbances caused by the insertion of the vibrating rod, monitoring horizontal stresses at various depths. Both laboratory and field tests show significant improvements: soil dry density increased by 8% to 18%, porosity decreased by 10% to 23%, compression modulus increased by 22% to 246%, and compression coefficient decreased by 8% to 70%. Additionally, cohesion (C) and angle of friction (ɸ) saw increases ranging from 7 to 38% and 3% to 25%, respectively. Below a depth of 3 m, cone tip resistance exceeded 10 MPa, and sidewall friction resistance increased to over 100 kPa, surpassing pre-treatment values. The standard penetration test results doubled stroke length compared to pre-treatment, indicating a substantial improvement in foundation bearing capacity. Surface wave tests before and after treatment showed a 15% increase in wave velocity, reflecting a more compact soil structure. The vibrating rod compaction method is innovative, energy-efficient, environmentally friendly, and economically beneficial, holding great potential for future miscellaneous fill treatments.